To Push or To Clip: That is the Question - Stephen H. Futch; James H. Graham; Larry W. Duncan (EDIS)
HS-1065, a 4-page illustrated fact sheet by Stephen H. Futch, James H. Graham, and Larry W. Duncan, reviews and evaluates the benefits and drawbacks of two methods of removing diseased or unproductive trees -- pushing the tree down and removing the entire tree and root systems, or clipping the tree off above the soil line. It describes the results of a study initiated in 2002 to investigate concerns about the push and clip methods.  Published by the UF Department of Horticultural Sciences, June 2006.